2011
DOI: 10.1177/0892705711408160
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of Fusion Bonding for Carbon Fabric Reinforced Polyphenylene Sulphide by Hot-Tool Welding

Abstract: In recent years, there is a growing interest in joining techniques for thermoplastic composites as an alternative to adhesive bonding. In this manuscript, a fusion bonding process called hot-tool welding is investigated for this purpose and the used material is a carbon fabric reinforced polyphenylene sulphide. The welds are first observed through a microscope, after which the quality is experimentally assessed using a short three-point bending setup. A comparison is made between the welded specimens and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…These authors moved further to examine the inter‐laminar behavior of a carbon fabric reinforced PPS by using lap experiments and they considered several loading conditions. The results showed that no crack growth was observed , both under quasi‐static loading until failure and successive loading‐unloading stages with increasing maximum load. Kytýr et al also evaluated impact damage effect on residual fatigue life of PPS composites reinforced by carbon fibers.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…These authors moved further to examine the inter‐laminar behavior of a carbon fabric reinforced PPS by using lap experiments and they considered several loading conditions. The results showed that no crack growth was observed , both under quasi‐static loading until failure and successive loading‐unloading stages with increasing maximum load. Kytýr et al also evaluated impact damage effect on residual fatigue life of PPS composites reinforced by carbon fibers.…”
Section: Introductionmentioning
confidence: 96%
“…As a good engineering thermoplastic material, PPS/GF composites show excellent mechanical properties and fatigue performance. In fact, there are a wide range of reports concerning this issue . Some researchers pay attention to PPS composites with different types of reinforcements.…”
Section: Introductionmentioning
confidence: 99%
“…This test has the advantage that it requires a lot less material than for the lap shear or mode I DCB test and it is a very simple test; force and displacement already give plenty of information. Also, this setup induces an interesting stress distribution in the bond, as was seen by finite element modelling in ABAQUS™ [10].…”
Section: Introductionmentioning
confidence: 96%
“…The fusion bonding of pure thermoplastics is already a well known and commonly applied production process, but the process parameters cannot be extrapolated to the welding of fibre-reinforced thermoplastics, since the reinforcement has a large influence: the material is no longer isotropic, head conduction is influenced … In general, these fusion bonding techniques can be categorised in three groups [1]: (i) frictional welding, including ultrasonic welding [2,3]; (ii) electromagnetic welding, including resistance welding [4, 5, 6,] and induction welding [7,8] and (iii) thermal welding, including infrared welding [9] and hot-tool welding [10].…”
Section: Introductionmentioning
confidence: 99%
“…A última categoria é a soldagem térmica (ou de duplo-estágio), onde o calor é aplicado diretamente na superfície a ser soldada, seguido da aplicação de pressão ao sistema para manter as partes unidas (DE BAERE et al, 2012 …”
Section: Principais Metodologias De Soldagemunclassified